Prescription audit study in a tertiary care hospital using the anatomical therapeutic chemical and defined daily dose classification concept - Gupta, Ajay Kumar; Mishra, Siddhartha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: In 1996, WHO recognized the need to develop and use the anatomical therapeutic chemical (ATC) and defined daily dose (DDD) as an international standard for utilization studies wherein it appointed experts in clinical pharmacology, drug utilization, drug regulation, drug evaluation, statistics, and medicine to monitor drug utilization on a standard and uniform pattern around the world. Methods: All the prescriptions presented to main dispensary of the hospital from January-December 2013 in mid-month period of 10 days were taken for the analysis in terms of pharmacovigilance, polypharmacy, drug usage group wise, pharmacoeconomics, and drug utilization in DDD/1000/day along with ATC classification using customized software. Results: 35,808 prescription forms containing 121, 303 drugs were presented to main dispensary of the hospital across which medicines were dispensed. Polypharmacy was calculated to be 3.27±0.44 standard deviation. Approximately, 60% of total prescription forms analyzed were lacking essential and basic such information as age, gender, or diagnosis. Pharmacoeconomics of this study indicates that a major budget was mainly spent on drug groups belonging to - metabolic, antibiotics, hormones, and related drugs. A voluminous consumption of drugs belonged to drug groups - metabolic drugs like statins, hormones, and related drugs such as various oral hypoglycemics, anti-hypertensives, psychotropics, and proton pump inhibitors or H2 blockers, all indicative toward stressful and sedentary lifestyle of modern era and unhealthy lifestyles, a trend of increasing morbidity and mortality, reducing significantly the productive man-hours. Conclusions: This study was undertaken in a government tertiary care hospital which gives insight into the day to day functioning status of our health care delivery system. It is an opportunity on self-assessment in further improving the health care delivery by implementing measures which economizes on scarce health care budget as well as minimizing the common prescription errors.